29. KNOWLEDGE OF STANDARD PRECAUTIONS AMONG HEALTHCARE PROFESSIONALS AT THANH HOA LUNG HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the knowledge of healthcare professionals regarding the implementation of specific standard precautionary measures at Thanh Hoa Lung Hospital in 2024.Subjects and methods: A cross-sectional descriptive study was conducted with a sample of 260 healthcare professionals at Thanh Hoa Lung Hospital from March 2024 to June 2024.Results: The proportion of healthcare professionals correctly identifying the sequence of hand hygiene steps was 81.2%. Knowledge regarding hand hygiene practices within standard precautions ranged between 89.6% and 98.8%. Regarding personal protective equipment, correct knowledge varied notably: mandatory occasions for mask usage were correctly identified by 18.8%, the efficacy of surgical masks by 66.9%, and the primary purpose of mask usage by 46.9%. Additionally, correct understanding of personal protective equipment usage procedures-including objectives to protect healthcare workers, patients, and the community, and knowledge of various personal protective equipment items (gowns, caps, goggles, face shields, gloves, masks) ranged from 91.9-92.7%, respectively.Conclusion: The majority of healthcare professionals demonstrated good knowledge concerning standard precautions, although deficiencies remain in certain precautionary measures. However, some healthcare workers still have limited knowledge about the use of personal protective equipment, which needs to be improved.
Keywords: Knowledge; healthcare workers; standard precautions